Marketing Strategy of PT Usaha Makmur Indonesia in Increasing Sales and Company Competitiveness - Muslikun; Miya Dewi Suprihandari (Journal of Economics, Management, Accounting, Business, Educational, Technology, and Social Science, 2024)
This research aims to analyze the marketing strategies implemented by PT Usaha Makmur Indonesia to increase sales and competitiveness in a competitive market. The research approach used is qualitative with a case study method. Data was collected through in-depth interviews with marketing management and analysis of company documents, including sales reports and marketing strategies. The research results show that PT Usaha Makmur Indonesia implements a digital marketing strategy that includes the use of social media, content marketing, and online advertising campaigns that are effective in increasing brand visibility and interaction with consumers. Additionally, the company is also adopting a data-driven approach to understand customer needs and optimize loyalty programs. The implication of this strategy is a significant increase in sales and a strengthening of competitive position in the market. This research concludes that innovation in digital marketing and a focus on customer satisfaction are key success factors in improving the marketing performance of PT Usaha Makmur Indonesia.